Bacterial leakage assessment in root canals sealed with AH Plus sealer modified with silver nanoparticles - Farzaneh Afkhami (BMC, 2021)
Abstract Background Successful endodontic therapy requires prevention of bacterial leakage between the root canal filing and root-canal walls. Sealing quality of a root canal filling depends strongly on the sealing ability of the sealer used. The present study aimed to evaluate the bacterial leakage resistance of AH Plus sealer modified with silver nanoparticles. Methods Forty sound teeth were obturated using lateral compaction technique except for five teeth as the negative controls. After considering five teeth as the positive controls (filled without sealer), the remaining teeth were assigned to two groups (n = 15) in terms of the sealer used (AH Plus sealer and silver nanoparticle-modified AH Plus). Bacterial leakage was evaluated in saliva using the two-chamber technique in every 24 h. When all the samples in the test groups were contaminated, the study was terminated. The data were analyzed with log-rank statistical test. Results All samples in both experimental groups were contaminated during the 3-months period of observation. There was no significant difference in contamination time between study groups (P > 0.05). Conclusions Silver nanoparticles used in tested concentration did not improve the bacterial leakage resistance of AH Plus sealer.